Coupling Phenomena in Magnetocaloric Materials. Issue 8 (5th August 2018) - Waske, Anja; Dutta, Biswanath; Teichert, Niclas; Weise, Bruno; Shayanfar, Navid; Becker, Andreas; Hütten, Andreas; Hickel, Tilmann
Abstract: Strong coupling effects in magnetocaloric materials are the key factor to achieve a large magnetic entropy change. Combining insights from experiments and ab initio calculations, we review relevant coupling phenomena, including atomic coupling, stress coupling, and magnetostatic coupling. For the investigations on atomic coupling, we have used Heusler compounds as a flexible model system. Stress coupling occurs in first‐order magnetocaloric materials, which exhibit a structural transformation or volume change together with the magnetic transition. Magnetostatic coupling has been experimentally demonstrated in magnetocaloric particles and fragment ensembles. Based on the achieved insights, we have demonstrated that the materials properties can be tailored to achieve optimized magnetocaloric performance for cooling applications. Abstract : Stronger together : Coupling effects in magnetocaloric materials are the key factor to achieve large magnetic entropy changes und hence a large magnetocaloric effect. Combining experimental techniques with ab initio calculations, we have explored relevant coupling phenomena and ways to tailor magnetocaloric materials to achieve the best performance for cooling applications.